The photo-electrocatalytic property of hollow mesoporous graphene oxide/tungsten trioxide/titanium dioxide membrane photo-anode - Yuan Li; Xinying Sun; Jiajia Chen; Shuping Luo; Guohua Li (Heliyon)
Titania (TiO2) is one of promising photo catalysts for its high ability to resistant photo corrosion and environmental friendliness, but its photocatalytic activity is too low to be used in industry. To find an approach to solve this problem, graphene oxide (GO), tungsten trioxide (WO3) and TiO2 composite with hollow mesoporous structure was prepared by a two-step spray drying method. The composite was used as raw material to constitute a membrane onto ITO glass to form a membrane photo-anode. In this way, its photo-electrocatalytic property was tested. The morphology, crystal phase, microstructure and specific surface area of the composite were characterized by SEM, XRD, TEM and BET, respectively. The surface potential distribution and optical property of the anode were measured by a Kelvin Probe Force Microscopy and a Fs-5 Steady-State Fluorescence Spectrometer, respectively. The forbidden bandwidth of the GO-WO3/TiO2 composite is 2.30 eV, which is much lower than that of the WO3/TiO2 composite, 2.92 eV. When the content of GO in the anode is around 1 wt%, its light absorption ability is the best among all the anodes with different contents of GO, and its photocatalytic ability to degrade methyl orange is the strongest as our experiments concerned. These findings indicate that the addition of GO into the WO3/TiO2 composite can improve its photo-electrocatalytic property. The construction of membrane photo-anode is an efficient approach to solve the problem of the recovery and secondary utilization of nanoscale powder in water treatment.